The poplar VQ1 gene confers salt tolerance and pathogen resistance in transgenic Arabidopsis plants via changes in hormonal signaling. Issue 4 (23rd February 2022) - Liu, Shifan; Wang, Zhaocheng; Wu, Jing; Wu, Caijuan; Xiong, Rui; Xiang, Yan; Yan, Hanwei
Abstract: The VQ protein family is plant-specific, and is involved in growth, development, and biotic and abiotic stress responses. In this study, we found that the gene expression of poplar VQ1 (Potri.001G029700) from Populus trichocarpa varied remarkably under salt stress and hormones associated with disease. A subcellular localization experiment showed that VQ1 was localized in the nucleus and cytomembrane in tobacco. The overexpression of VQ1 in Arabidopsis thaliana enhanced its resistance to salt stress and disease, and was also responsive to it through abscisic acid. Compared with wild-type, transgenic Arabidopsis lines had significantly increased levels of abscisic acid and salicylic acid. The expression of some stress-related genes, such as MPK6, NPR1, and PDF1.2, was significantly up-regulated by salt in transgenic plants, while WRKY70, ABI1, KUP6, and NCED2 were significantly down-regulated by Pseudomonas syringae pv. tomato DC3000 in transgenic plants. Together, these results demonstrate that VQ1 modulates hormonal signaling to confer multiple biotic and abiotic stress responses in transgenic Arabidopsis plants.